Two New Nonsense Mutations in Type Ia Antithrombin III Deficiency at Leu 140 and Arg 197 - Tomonari, Akira; Iwahana, Hiroyuki; Yoshimoto, Katsuhiko; Shigekiyo, Toshio; Saito, Shiro; Itakura, Mitsuo (Thrombosis and Haemostasis, 1992)
Using polymerase chain reaction-single strand conformation polymorphism (PCR-SSCP) and DNA sequencing, the molecular basis of hereditary type la antithrombin III (AT III) deficiency was disclosed in two families. One mutation was a change from T to A in the codon of TTA for Leu 140 forming a stop codon of TAA, which was confirmed by mutated primer-mediated PCR-HindIII digestion. The application of this method demonstrated that all four affected members had the mutant allele in a heterozygous state and that none of unaffected subjects had this mutation. Another mutation in the second family was a change from C to T in the codon of CGA for Arg 197 also forming a stop codon of TGA, which was confirmed by PCR-HaeIII digestion. Based on these, it was concluded that the two new nonsense mutations in the AT III gene in a heterozygous state are the molecular basis of hereditary type Ia AT III deficiency.